Separation of gas and dust in the winds of AGB stars. Issue Volume 14:Issue S343(2019) (August 2018) - Mattsson, Lars; Sandin, Christer; Ventura, Paolo
Abstract: We present first results from a project aiming at a better understanding of how gas and dust interact in dust-driven winds from Asymptotic Giant Branch (AGB) stars. We are at the final stage of developing a new parallelised radiation-hydrodynamics (RHD) code for AGB-wind modelling including a new generalised implementation of drift. We also discuss first results from high-resolution box simulations of forced turbulence intended to give quantitative "3D corrections" to dust-driven winds from AGB stars. It is argued that modelling of dust-driven winds of AGB stars is a problem that may need to be treated in a less holistic way, where some parts of the problem are treated separately in detailed simulations and are parameterised back into a less detailed (1D spherically symmetric) model describing the entire picture.